Ressonâncias da representação do trabalho camponês medieval na arte de Jean-François Millet (1814-1875) - Silva, Paula de Souza Santos Graciolli (2017)
This dissertation deals with the representation of the peasant in medieval artistic objects and in the paintings of the romantic / realistic artist Jean-François Millet (1814-1875). The objectives of this research consist into establish parallels between